Legal Analysis of the Application of Restorative Justice in Narcotics Abuse Offenses Involving Minors - Ma’ruf, Tri Abriana; Buana, Andika Prawira; Saputra, Novriyanto Ricky; Suhra, Andi Amalia (Golden Ratio of Data in Summary, 2024)
This research aims to determine and analyze restorative justice arrangements in criminal acts of narcotics abuse for children as well as obstacles and solutions in implementing restorative justice in criminal acts of narcotics abuse for children. The research method used in this research is normative juridical. The results of this research show that restorative justice in handling and resolving narcotics crimes committed by children and efforts to resolve problems related to the use of diversion tactics in juvenile narcotics crimes in general have not run optimally in accordance with the provisions of Law Number 11 of 2012 concerning the justice system. children and the formal criminal justice system. Research recommendations to law enforcement officials that it is best to implement Restorative Justice in handling criminal acts of narcotics abuse by children in Indonesia should take a comprehensive approach.